Clinical Experience of the Application of Intravenous Therapy with VIT. C, Ozonotherapy and Biomagnetic Therapy - Damyanov, Dr. Chr.; Pavlov, Dr. Vl.; Todorov, Dr. Al.; Pashina, Iv. (International Journal of Scientific Research and Management (IJSRM), 2023)
On the background of the announced COVID-19 pandemic, the treatment of seasonal viral infections demonstrates a serious irrational approach by ignoring numerous scientific publications about methods from the arsenal of integrative medicine. Among these methods stand out: intravenous vitamin C application in high doses, Ozone therapy and Scalar Biomagnetic therapy (SBT) with magnetic pairs. After a thorough review of a number of scientific publications and based on our clinical experience of the application of these methods in oncological diseases, we have prepared our own protocol for the treatment of viral diseases including these three methods. The protocol was prepared in January 2021. In this publication, we present the first results using this method for the treatment of oncological and viral diseases,